Parasiticidal Properties of Nanoemulsion-Based Plant Essential Oil Formulations for Controlling Poultry Ectoparasites in Farm Conditions - Jarongsak Pumnuan; Anuwat Lakyat; Ampon Klompanya; Duangkamol Taemchuay; Amorn Assavawongsanon; Thanaporn Doungnapa; Somsak Kramchote (Insects)
Nanoemulsion-based plant essential oil formulations (NEOFs) have shown remarkable parasiticidal properties in laboratory settings, suggesting the potential for practical farm applications. This study investigates the efficacy of NEOFs—comprising clove and cinnamon essential oils (EOs)—in controlling poultry ectoparasites under real farm conditions. We evaluated the impact of NEOFs on ectoparasite populations, egg-laying performance, egg quality, leukocyte profiles in chicken blood, and potential insecticide residues in eggs. Conducted across various poultry farms, the results revealed that NEOFs achieved an over 95% ectoparasite eradication after two treatments, compared to significantly higher ectoparasite populations in untreated control groups. Egg production was notably higher in NEOF-treated flocks, and the feed conversion ratio was improved. No significant differences in leukocyte profiles were observed between the treated and control groups. In contrast, cypermethrin residues were detectable in eggs for more than eight weeks post-treatment. NEOFs achieved an over 97% ectoparasite extermination within seven days post-treatment, with farmer satisfaction averaging 4.83 out of 5.00. These findings position NEOFs as a highly effective, environmentally friendly alternative to chemical pesticides for managing poultry ectoparasites, offering a viable solution for sustainable poultry farming.